Specific features of EU external relations law (International relations and international law Journal, 2016)
The issue discussed in this article is the EU law in its external relationsafter the entry into force of the Treaty of Lisbon. In the law of EU in external actions there are some special features and exceptions which are found only after comparing the provisions of TEU and TFEU, and analyzing the practice of exercising EU its competences. Although the Lisbon Treaty recently expanded the scope of external exclusive EU competence, there are some exceptional moments, as in transport policy which is outside the scope of the CCP and the external competence is shared between the EU and the Member States or the Development policy which is exercised under shared competence, albeit with the caveat that the exercise of EU competence in relation to development cooperation and humanitarian aid does not pre-empt the Member States from exercising their competence. The broad scope of CFSP gives rise to the question about a borderline between the CFSP and other external policies of the EU. The title of conclusion of international agreements also has exceptional moment in area of mixed agreements which is made on the basis of the EU and Member State’s joint participation.
Keywords: EU law; external competence; CFSP; international agreements